One-stone-for-two-birds strategy to attain beyond 25% perovskite solar cells - Yang, Tinghuan; Gao, Lili; Lu, Jing; Ma, Chuang; Du, Yachao; Wang, Peijun; Ding, Zicheng; Wang, Shiqiang; Xu, Peng; Liu, Dongle; Li, Haojin; Chang, Xiaoming; et al. (Nature communications, 2023)
Even though the perovskite solar cell has been so popular for its skyrocketing power conversion efficiency, its further development is still roadblocked by its overall performance, in particular long-term stability, large-area fabrication and stable module efficiency. In essence, the soft component and ionic–electronic nature of metal halide perovskites usually chaperonage large number of anion vacancy defects that act as recombination centers to decrease both the photovoltaic efficiency and operational stability. Herein, we report a one-stone-for-two-birds strategy in which both anion-fixation and associated undercoordinated-Pb passivation are in situ achieved during crystallization by using a single amidino-based ligand, namely 3-amidinopyridine, for metal-halide perovskite to overcome above challenges. The resultant devices attain a power conversion efficiency as high as 25.3% (certified at 24.8%) with substantially improved stability. Moreover, the device without encapsulation retained 92% of its initial efficiency after 5000 h exposure in ambient and the device with encapsulation retained 95% of its initial efficiency after >500 h working at the maximum power point under continuous light irradiation in ambient. It is expected this one-stone-for-two-birds strategy will benefit large-area fabrication that desires for simplicity. Long-term stability and stable efficiency are essential for large-area fabrication of perovskite solar cells. Here, the authors achieve in situ anion-fixation and undercoordinated-Pb passivation using amidino-based ligand, realizing maximum power conversion efficiency of 25.3% with T95 over 500 h.